2020
DOI: 10.3390/fi12120216
|View full text |Cite
|
Sign up to set email alerts
|

An Extended Car-Following Model Considering Generalized Preceding Vehicles in V2X Environment

Abstract: Vehicle-to-everything (V2X) technology will significantly enhance the information perception ability of drivers and assist them in optimizing car-following behavior. Utilizing V2X technology, drivers could obtain motion state information of the front vehicle, non-neighboring front vehicle, and front vehicles in the adjacent lanes (these vehicles are collectively referred to as generalized preceding vehicles in this research). However, understanding of the impact exerted by the above information on car-followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 43 publications
(64 reference statements)
0
12
0
Order By: Relevance
“…With the aforementioned connected technologies enabled by fifth generation mobile networks, drivers can obtain motion state information of multiple preceding vehicles including the left/right preceding vehicle. According to this, we proposed a generalized preceding vehicles (GPV) model, which can describe drivers' car-following behavior with consideration of GPV information in a relatively accurate way, in the previous research [33]. The research results confirmed the stabilizing effect of GPV information on traffic flow.…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations
“…With the aforementioned connected technologies enabled by fifth generation mobile networks, drivers can obtain motion state information of multiple preceding vehicles including the left/right preceding vehicle. According to this, we proposed a generalized preceding vehicles (GPV) model, which can describe drivers' car-following behavior with consideration of GPV information in a relatively accurate way, in the previous research [33]. The research results confirmed the stabilizing effect of GPV information on traffic flow.…”
Section: Introductionmentioning
confidence: 71%
“…Although there are multiple extended models mentioned in Section 1 with consideration of the impacts exerted by the motion state information of an arbitrary number of preceding vehicles in the current lane, there was no research considering the influence caused by preceding vehicles in the adjacent lanes, of which information is available for the driver in the V2X environment. Based on these, we considered the motion state information of GPV, which consists of the preceding vehicle, the non-neighboring preceding vehicle and the left/right preceding vehicle in the adjacent lanes, and proposed an extended model named the GPV model [33]. The equation of this model is as follows:…”
Section: Simulation Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, with the road as a vehicle carrier, the I-VICS uses advanced wireless communication technology and sensing detection technology. The purpose of I-VICS is to obtain data from vehicle-to-vehicle (V2V), vehicle-to-infrastructure (V2I) sensing devices, and other related information to realize the fusion of heterogeneous data from multisource, as well as to share the information to achieve reasonable speed and lane-changing behavior suggestions during vehicle operation so that viatic traffic can develop regarding intelligence, networking, and automation [4][5][6]. Therefore, in the I-VICS environment, more effective information can be transmitted to the driver to improve the correctness and systematization of driving decisions, especially in dynamic traffic control.…”
Section: Introductionmentioning
confidence: 99%